Lipid distribution on ethnic hairs by Fourier transform infrared synchrotron spectroscopy. Issue 1 (21st September 2021) - Barba, Clara; Oliver, Marc Adria; Martí, Meritxell; Kreuzer, Martin; Coderch, Luisa
Abstract: Background: A synchrotron‐based Fourier transform infrared micro‐spectrometer (μ‐FTIR) allows the spatial determination of lipids across the different layers of ethnic hairs and differentiates between the lipid order arrangement and quantity. Materials and methods: The three ethnic fibers were delipidized, the lipid extracts were characterized, and the delipidized fibers were studied by dynamic vapor sorption experiments (DVS) and FTIR‐synchrotron techniques. Results: The average spectra from the different hair regions exhibited the most intense CH2 sym peaks on the medulla, followed by those from the cuticle and cortex for all hairs of different ethnicities. Differences in the lipid fraction of the three hair types have been observed, and they can explain some barrier properties. African virgin hair was demonstrated to have more lipids mainly in the medulla, which implies an important hydrophobicity with low hysteresis between absorption and desorption water vapor processes. In addition, these lipids are highly disordered, mainly in the cuticle, which can be related to its high water vapor diffusion. Asian and Caucasian virgin hairs presented a similar lipid order in all regions, with similar diffusion coefficients. Results indicate that the higher order of the lipid bilayer hinders water permeation kinetics in some way. Conclusion: The differences in the presence and organization of the lipids in the different regions of the African hair can account for its differentiation with regards to moisturization and swelling from the other types of fibers.